Pengaruh Lingkungan Keluarga, Teman Sebaya, dan Prestasi Belajar Terhadap Minat Melanjutkan Pendidikan ke Perguruan Tinggi Siswa SMK Negeri Bisnis dan Manajemen Kota Padang - Rena Cahyati; Bustari Muchtar (Jurnal Ecogen, 2019)
This research aims to determine the extent of the influence of family environment, peers, and learning achievement on the interest in continuing education to higher education in the XI class of accounting skills competencies in Padang City Vocational School simultaneously and partially. There are two Vocational Schools namely Padang State Vocational High School 2 and Padang State Vocational High School 3. This means that the population in this study was all students of class XI Accounting of Vocational Schools 2 Padang, amounting to 121 people and Vocational Schools 3 Padang totaling 83 people. From a total of 204 populations, the sampling method used was proportional random sampling technique with a total sample of 127 students. Data collection techniques using questionnaires and documentation. For data analysis methods used are descriptive and associative analysis and hypothesis testing using multiple linear regression analysis. The results of the study showed that there were influences on the family environment, peers, and learning achievement towards the interest in continuing to higher education simultaneously at 24.8%. Partially the family environment influences the interest in continuing to higher education. Whereas peers do not influence the interest in continuing their education to college. Likewise, for learning achievement does not affect the interest in continuing to higher education.Keyword: family environment, peers, learning achievement